Kawasaki disease in Australia, 1993–95. Issue 1 (1st January 1998) - Royle, Jennifer A; Williams, Katrina; Elliott, Elizabeth; Sholler, Gary; Nolan, Terry; Allen, Roger; Isaacs, David
Abstract : AIM: To describe the epidemiology, management, and rate of cardiac sequelae of Kawasaki disease in Australia. DESIGN: Cases were notified to the Australian Paediatric Surveillance Unit, an active national surveillance scheme, from May 1993 to June 1995. RESULTS: 139 cases of Kawasaki disease were confirmed. In 1994, the annual incidence was 3.7/100 000 children < 5 years old. Sixteen children were not admitted to hospital. Coronary artery abnormalities were reported in 35 (25%) children. Two patients were diagnosed at postmortem examination. Sixty six per cent of patients were diagnosed within 10 days of onset and 81% of these received intravenous gammaglobulin within 10 days. Forty five of the notified children did not fulfil the study criteria because of streptococcal infection or insufficient clinical criteria. One child with streptococcal infection had coronary artery dilatation. CONCLUSION: Diagnosis of Kawasaki disease was delayed beyond 10 days in one third of patients, and almost 20% of children who could have received gammaglobulin within 10 days did not. The distinction between Kawasaki disease, streptococcal infection, and other possible diagnoses is problematic in some children.